Interdisciplinarity and Universality of Foreign Languages Education - Rusudan Makhachashvili; Ivan Semenist (Journal of Systemics, Cybernetics and Informatics, 2021)

(untitled)
Transformative potential of the knowledge economy of the XXI century, establishment of networked society, emergency digitization due to the COVID-19 pandemic measures have imposed elaborate interdisciplinary and transdisciplinary demands on the marketability of Liberal Arts university graduates' skills and competences, upon entering the workforce. The study is focused on the in-depth diagnostics of the development of multipurpose orientation, universality and interdisciplinarity of skillsets for students of European (English, Spanish, French, Italian, German) and Oriental (Mandarin Chinese, Japanese) Languages major programs through the span of educational activities in the time-frame of COVID-19 quarantine measures of March 2020 to January 2021. A computational framework of foreign languages education interdisciplinarity is introduced in the study. The survey analysis is used to evaluate the dimensions of interdisciplinarity, universality and transdiciplinarity, informed by the interoperability of soft skills and digital communication skills for Foreign Languages Education across contrasting timeframes and stages of foreign languages acquisition and early career training.